SweDia 2000 Research Database - Eriksson, Anders; Lingvistik, Språk- och litteraturcentrum, Lund University; Department of Philosophy and Linguistics, Umeå University; Department of Linguistics, Stockholm university (Information not available, contact SND for more information, 2021)
The material was collected in two databases- one for research and one for the general public. The Research Database will be available to researchers in linguistics, Scandinavian languages, etc. The general database is addressed to interested individuals, schools, libraries, etc. Regardless of whether you are a researcher, student, private individual or anything else, the material cannot be used for any other purpose than research and/or education.

The research database consists of recordings of a little more than 1300 speakers representing 107 Swedish dialects. The durations of the recordings vary between 25 minutes and over one hour (typically 30 to 40 minutes). Each recording consist of two major parts. One part consisting of controlled material where specific aspects of Swedish phonology are elicited and one part containing spontaneous speech in the form of informal interviews or dialogues between two speakers of the dialect. The controlled material was elicited by the interviewers using crossword like word games in order to avoid any influence of the interviewers own pronunciation of the target words. The material has three parts 1) A wordlist containing words from which the vowel and consonant systems of the dialect can be derived, 2) a wordlist from which the phonological quantity system may be derived and, 3) a list of phrases from which stress and accent patterns may be derived. Typical durations of the controlled and spontaneous material are 10-15 minutes and 15-25 minutes respectively. Database format: The research database is hosted on a server at the Centre for Languages and Literature at Lund University. The meta data standard used for the database is the one defined by the ISLE Meta Data Initiative (IMDI).- utkast

Purpose:
The purpose is to document and study a large number of Swedish dialects as they sound around the turn of the century 2000. The documentation is done through recordings of dialect speakers for a total of 107 locations in Sweden and in the Swedish-speaking areas of Finland and on Åland.

Archiving:
The material can be found at the Dialect Archive in Gothenburg (DAG). For more details about DAG, visit: https://www.isof.se/om-oss/kontakt/avdelningen-for-arkiv-och-forskning-i-goteborg.html

Materialet har samlats i två databaser- en för forskning och en avsedd för intresserad allmänhet. Forskningsdatabasen ska vara tillgänglig för forskare inom lingvistik, nordiska språk med mera. Den allmänna databasen riktar sig till intresserade privatpersoner, skolor, bibliotek, studieförbund och liknande. Oavsett om man är forskare, student, privatperson eller annat kan materialet ej användas för annat ändamål än forskning och/eller undervisning.

Forskningsdatabasen består av inspelningar av lite mer än 1300 talare som representerar 107 svenska dialekter. Varaktighetema för inspelningarna variera mellan 25 minuter och under en timme (typiskt 30 till 40 minuter). Varje inspelning består av två huvuddelar. En del bestående av kontrollerad material där specifika aspekter av den svenska fonologi framkallas och en del som innehåller spontant tal i form av informella intervjuer eller dialoger mellan två talare av dialekten. Den kontrollerade materialet tas fram av intervjuarna med korsordet som ordlekar för att undvika påverkan av intervjuarnas eget uttal av orden. Materialet har tre delar 1) en ordlista med ord från vilken vokal-och konsonant system i dialekten kan härledas, 2) en ordlista som den fonologiska mängden systemet kan härledas, och 3) en förteckning över fraser som stress och accent mönster kan härledas. Typiska tider på det kontrollerade och spontana materialet är 10-15 minuter respektive 15-25 minuter. Databasformat: forskningsdatabasen finns på en server vid Centrum för språk och litteratur vid Lunds universitet. Metadatastandard som används för databasen är den som definieras av Isle Meta Data Initiative (IMDI). -utkast

Syfte:
Syftet är att dokumentera och studera ett stort antal svenska dialekter såsom de låter runt sekelskiftet 2000. Dokumentationen sker genom inspelningar av dialekttalare på sammanlagt 107 orter i Sverige och i de svensktalande områdena i Finland samt på Åland.

Arkivering:
Materialet finns hos dialektarkivet i Göteborg (DAG). För mer information om DAG, se: https://www.isof.se/om-oss/kontakt/avdelningen-for-arkiv-och-forskning-i-goteborg.html
SweDia 2000 forskningsdatabas
Keywords: languages; språk; language; språkliga uttryck; dialects; dialekter; language variations; språkvariationer; speach; tal; acoustics; akustik; accent; accent; intonation; intonation; phonetics; fonetik; phrasing; frasering; Language and linguistics; Språk och lingvistik; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik